Probing Higgs-portal dark matter with weakly Interacting mediators - Westhoff, Susanne (Arxiv, 2016)
The hypothesis of dark matter interacting with the standard model uniquely via the Higgs portal is severely challenged by experiments. However, if dark matter is a fermion, the Higgs-portal interaction implies the presence of mediators, which can change the phenomenology significantly. This article discusses the impact of weakly-interacting mediators on the dark-matter relic abundance, direct detection, and collider searches. At the LHC, a typical signature of Higgs-portal fermion dark matter features soft leptons and missing energy, similarly to gaugino production in models with supersymmetry. We suggest to re-interpret existing gaugino searches in the context of Higgs-portal models and to extend future searches to the broader class of dark sectors with weakly-interacting fermions.